Single Cell RNA Sequencing Reveals Critical Functions of Mkx in Periodontal Ligament Homeostasis - Takada, Kaho; Chiba, Tomoki; Miyazaki, Takayuki; Yagasaki, Lisa; Nakamichi, Ryo; Iwata, Takanori; Moriyama, Keiji; Harada, Hiroyuki; Asahara, Hiroshi (Frontiers in Cell and Developmental Biology, 2022)
The periodontal ligament (PDL) comprises a fibrous tissue that connects teeth to alveolar bone and is essential for periodontal function. The transcription factor mohawk homeobox (Mkx) is expressed in the PDL where it plays an important role in the development and maintenance of the PDL. However, the precise and critical functions of Mkx in the cell populations comprising PDL have not yet been elucidated. The present study aimed to clarify the effects of a Mkx deficiency on PDL cellular heterogeneity and differences between gene expression in PDL tissues from wild-type (WT) (Mkx+/+) and Mkx knockout (Mkx-/-) rats using single-cell RNA sequencing. We identified 12 cell clusters comprising mesenchymal cells and macrophages. The expression of Mkx and scleraxis (Scx; another key transcription factor of PDL), was mutually exclusive, and partitioned mesenchymal cell clusters into Mkx and Scx types that dominantly expressed proteoglycans and elastic fibers, and type 1 and 3 collagen, respectively. Ossification-related genes were upregulated in mesenchymal cell and osteoblast clusters with more Mkx-/- than Mkx+/+ PDLs. Increased number of cells and inflammatory mediators were observed in Macrophage clusters of Mkx-/- PDL. These results suggested that Mkx plays an important role in maintaining PDL homeostasis by regulating specific cell populations and gene expression.